Variability and phase lags of the type-C quasi-periodic oscillation of MAXI J1348-630 with NICER - Alabarta, Kevin (2022)
We study the properties of the type-C quasi-periodic oscillation (type-C QPO) of MAXI J1348-630 during its 2019 outburst and reflare with NICER. This is the first time that the evolution of the properties of type-C QPOs is studied during an outburst reflare. We found that the properties of the type-C QPO during the reflare are similar to those of type-C QPOs observed in other black hole systems during outburst. This suggests that the physical processes responsible for type-C QPOs are the same in a reflare and in an outburst. We also found that the full width at half-maximum of a high-frequency broad-band component observed during the reflare changes significantly with energy. We studied the energy-dependent fractional rms amplitude and phase lags of the type-C QPO from 0.5 to 12 keV. We found that the fractional rms amplitude increases up to 2-3 keV and then remains approximately constant above this energy, and the lag spectra of the type-C QPO are hard. We discuss the dependence of the fractional rms amplitude and phase lags with energy in the context of Comptonization as the radiative mechanism driving the QPO rms and lag spectra.